1995
DOI: 10.1007/bf01215205
|View full text |Cite
|
Sign up to set email alerts
|

Decentralizing lottery allocations in markets with indivisible commodities

Abstract: In economies with indivisible commodities, consumers tend to prefer lotteries in commodities. A potential mechanism for satisying these preferences is unrestricted purchasing and selling of lotteries in decentralized markets, as suggested in Prescott and Townsend [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, this paper shows in several examples that such lottery equilibria do not always exist for economies with finitely many consumers. Other conditions are needed. In the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…One may think why the price vector p ∆ = (1.65, 1.65) is not stable for (8). At these prices, we have that Thus, all Euler polygonal arcs of (8) will move away from the prices (1.65, 1.65) and never come back to it.…”
Section: Examplesmentioning
confidence: 98%
See 3 more Smart Citations
“…One may think why the price vector p ∆ = (1.65, 1.65) is not stable for (8). At these prices, we have that Thus, all Euler polygonal arcs of (8) will move away from the prices (1.65, 1.65) and never come back to it.…”
Section: Examplesmentioning
confidence: 98%
“…When the central network announces that the process begins, each agent starts to place his market order of an object bundle he is willing to buy at the prices p(t 0 ). Based on the new information of the market orders, the central network adjusts the prices according to (8). Then the process moves to period 1 and the new adjusted prices p(t 1 ) become the new market prices and are posted on each terminal.…”
Section: Figure 1 An Euler Price Iterative Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling economies with indivisibilities is therefore meaningful and realistic. However, studying such discrete economies stands in general a daunting challenge; see for example Koopmans and Beckman [13], Debreu [6], Henry [10], Kelso and Crawford [12], Gale [7], Quinzii [18], Shapley and Scarf [22], and Scarf [19,20,21], and more recently Kaneko and Yamamoto [11], Yamamoto [24], Shell and Wright [23], Garratt [8], Garratt and Qin [9], Ma [17], Bevia et al [1], Bikhchandani and Mamer [2], van der Laan et al [15], Yang [26]. In Danilov et al [5] it was shown that discrete convex analysis is an appropriate tool to deal with indivisibles.…”
Section: Introductionmentioning
confidence: 99%